The role of the social policy in supporting family stability in the Emirate of Sharjah: Analytical study for the period (2000-2020) - Himat, Makia Gomaa (Al-Adab Journal, 2022)
The current study aims to identify the role of social policy in achieving family stability in the Emirate of Sharjah, In the period (2000-2020) the uses the analytical and descriptive method. And employs a content analysis. The findings – 1-The issuance of many legislations distributed among the laws, decrees, decisions and administrative orders issued by government agencies, both at the federal and the local level in Sharjah, targeting the family and meeting all its needs, in addition to directives of his Highness the Ruler of Sharjah and his wife Sheikha Jawaher Al Qasimi, Chairman of the Supreme Council for Family Affairs in the emirate of Sharjah. 2- The existence of priority and care for family issues and the provision of decent living conditions through the Social Security Law, financial and material assistance for vulnerable families, in addition to directing privacy to the groups most in need of care within the family, so that Sharjah became within the international system and in accordance with of global standards of age-friendly and child-friendly cities. 3-The issuance of legislation supporting working mothers by directing the development of nurseries attached to work sites, applying flexible hours for mothers to take care of infants, and granting maternity and paternity leave. The study also shows supportive legislation to achieve family cohesion through the family counseling services affiliated with the Family Development Centers, one of the departments of the Supreme Council for Family Affairs, as all of this contributes to helping families achieve stability and cohesion. 4-Finaly the study revealed the weakness in the social statistics and the absence of updating data on the social and family reality in the emirate.